The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.3390/geosciences10100381
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Shale Source Rocks and Clay Mineral Diagenesis in the Permian Basin, USA: Inferences on Basin Thermal Maturity and Source Rock Potential

Abstract: The use of mineral diagenetic indices and organic matter maturity is useful for reconstructing the evolution of sedimentary basins and critical assessments for potential source rocks for petroleum exploration. In this study, the relationship of clay mineral diagenesis and organic matter thermal indices (Rock-Eval Tmax) and calculated vitrinite reflectance (%Ro) were used to constrain the maximum burial depths and temperatures of three distinct intervals within the northern Permian Basin, USA. X-ray diffraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 105 publications
(210 reference statements)
1
3
0
Order By: Relevance
“…This is consistent with previous studies (e.g. Green et al, 2020;Ferreiro-Mählmann et al, 2012 and references therein) which have demonstrated that clay minerals are slow to react to hydrothermal influences in comparison to organic matter.…”
Section: Controls On the Maturity Of The Fahdene And Bahloul Formation Source Rockssupporting
confidence: 93%
“…This is consistent with previous studies (e.g. Green et al, 2020;Ferreiro-Mählmann et al, 2012 and references therein) which have demonstrated that clay minerals are slow to react to hydrothermal influences in comparison to organic matter.…”
Section: Controls On the Maturity Of The Fahdene And Bahloul Formation Source Rockssupporting
confidence: 93%
“…Figure 1. A structural map of the Permian Basin on the left (modified from [13]) and stratigraphic columns on the right (after [14]). Figure 1.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…The outcome for core-extract samples (0.93 to 0.94 VREQ) are very similar to the result for extracted oil samples (~ 0.94 VREQ). Gas maturity which is conditioned on ethane / propane carbon isotopes (VREG) (GeoMark proprietary isotope/maturity calibration scale) has an average of approximately 0.93 for samples core head-space [11]. The average saturates/aromatics ratio samples and low asphaltenes sulfur provide evidence of high-quality oil and are aligned tothe API gravity of 42.0 deg.…”
Section: Conventional -The Lower Pennsylvanian Sandstone Playmentioning
confidence: 99%